Physicochemical characteristics and protein profile of oviductal and uterine fluids from domestic sheep - Vazquez-Avendaño, José Roberto; Cortez-Romero, César; Ambríz-García, Demetrio Alonso; Fortis-Barrera, María de los Angeles; Chávez-Ortega, Mara Patricia; Loza-Rodríguez, Hilda; Blancas-Flores, Gerardo; Navarro-Maldonado, María del Carmen (Austral Journal of Veterinary Sciences, 2024)
Oviductal (OF) and uterine (UF) fluids are a complex mixture of ions and macromolecules dissolved in water, derived from the secretions of secretory cells and transudates of the circulatory system. Through proteomics, OF and UF have been analyzed in different domestic species throughout the estrous cycle or during the first days of pregnancy. Therefore, the aim of this study was to evaluate the volume, osmolarity, concentration and distribution pattern of proteins, as well as the identification of OVGP1, HSP70 and ezrin proteins for their importance in reproductive physiology, in OF and UF from adult criollo type domestic sheep during the early luteal phase of the estrous cycle. An average of 3.2±1.5 μL OF and 17±0.5 μL UF per reproductive system were obtained; osmolarity was 343±20.8 mOsm kg-1 and 280±96.2 mOsm kg-1 and protein concentration was 71.9±23.8 g L-1 and 21.8±1.1 g L-1, respectively. In the protein distribution pattern, 20 bands were observed in the OF and 14 bands in the UF. Of these, 14 and 8 were specific for OF and UF, respectively, and 6 were common for both. The spectra of the protein molecular weights were 24–324 and 29–353 kDa for OF and UF, respectively. The presence of OVPG1, HSP70 and Ezrin proteins in both fluids was identified, being in greater quantity in the OF (P < 0.0005). The volume recovered from the UF was five times greater than that of the OF. Both osmolarity and protein concentration were higher in OF than in UF (1.2 and 3 times higher). The pattern of protein distribution between the OF and UF was different, being more complex in the OF. OVGP1, HSP70 and ezrin were identified in the OF and UF, and were found in greater quantities in the OF.